1979
DOI: 10.1159/000145149
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrastructural study of the optic nerves and visual cortices of young (2.5 months) and old (17 months) mice

Abstract: The aging optic nerves and visual cortices were studied in mice. Changes in the morphology of neuroglia were evident in the optic nerve but no difference in the numbers of neurotubules or myelin sheaths optic nerve fibers in the aged were observed. Large myelinated fibers, however, begun to degenerate. In the aging visual cortices, a higher proportion ofden-drodendritic contacts were present and microglia cells were found to be active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The aging of this system had been evaluated by morphological and morphomctrical means. Information gathered includes: (1) a decrease in cell volumes in the lateral geniculate bodies \ Yew and Ling Wong, 1981]: (2) a decrease in the number of large myelinated fibers in the optic nerve [Ling Wong et al, 1979]; (3) an in crease in glial activity and the proportion of dendrodendritic contacts in the visual cortices [Ling Wong et al. 1979], and (4) a variation in the size of phagosomes but no decrease in phagosome number [Yew, 1979: Yew andLing Wong, 1980], As it has been suggested that retinal response in old animals is exaggerated after light and dark adaptation [Yew, 1979], and that this response may be photic related [Lai et al, 1978], the retinal re sponse to photic injury was investigated in further detail in young and old albino mice.…”
Section: Introductionmentioning
confidence: 99%
“…The aging of this system had been evaluated by morphological and morphomctrical means. Information gathered includes: (1) a decrease in cell volumes in the lateral geniculate bodies \ Yew and Ling Wong, 1981]: (2) a decrease in the number of large myelinated fibers in the optic nerve [Ling Wong et al, 1979]; (3) an in crease in glial activity and the proportion of dendrodendritic contacts in the visual cortices [Ling Wong et al. 1979], and (4) a variation in the size of phagosomes but no decrease in phagosome number [Yew, 1979: Yew andLing Wong, 1980], As it has been suggested that retinal response in old animals is exaggerated after light and dark adaptation [Yew, 1979], and that this response may be photic related [Lai et al, 1978], the retinal re sponse to photic injury was investigated in further detail in young and old albino mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to housing the axons of RGCs the optic nerve also contains a variety of glial cells. Their diversity and population vary based upon the region of the optic nerve [41][42]. Glial cells play a major role in maintaining axonal health.…”
Section: Optic Nervementioning
confidence: 99%